Clean Graphene Surfaces: A Force‐Engineered Lint Roller for Superclean Graphene (Adv. Mater. 43/2019). Issue 43 (22nd October 2019) - Sun, Luzhao; Lin, Li; Wang, Zihao; Rui, Dingran; Yu, Zhiwei; Zhang, Jincan; Li, Yanglizhi; Liu, Xiaoting; Jia, Kaicheng; Wang, Kexin; Zheng, Liming; Deng, Bing; et al.
Abstract : A new approach to clean the surface of graphene is reported by Hailin Peng, Zhongfan Liu, and co‐workers in article number1902978, who use a force‐engineered "lint roller" to selectively removing the graphene's intrinsic surface contaminants. The as‐obtained super‐clean graphene can be transferred to dielectric substrates with significantly reduced polymer residues, and it exhibits superior electronic and optical properties such as ultrahigh carrier mobility and low contact resistance.